Implementasi Sekolah Ramah Anak (SRA) dalam rangka pemenuhan hak-hak anak pada SMP N 3 Ungaran Kabupaten Semarang Jawa Tengah - Purbonuswanto, Welius; Hadi, Sarbun; Hartanti, Christina Dwi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
The objectives to be achieved in this study are to find out, (1) Abstract: The objectives to be achieved in this research are to, (1) analyze the fulfillment of Child Friendly School indicators at SMP Negeri 3 Ungaran, Semarang Regency in order to fulfill children's rights. (2) Analyzing the successful implementation of the Child Friendly School Policy at SMP Negeri 3 Ungaran, Semarang Regency. (3) Analyze school constraints in implementing the Child Friendly School Policy. (4) Analyze the efforts made by schools in overcoming obstacles to the implementation of the Child Friendly School Policy to fulfill children's rights. The results showed that SMP Negeri 3 Ungaran had met the Child Friendly School indicators with very good criteria so that the children's rights to worship according to their religion, expression according to their level of intelligence, the right to education and teaching, the right to protection from the education unit were fulfilled. The implementation of the Child Friendly School Policy in the aspects of communication, resources, disposition and bureaucracy was very successful. Internal constraints include the presence of students who have not implemented SRA commitments, complaints from teachers and the infrastructure does not meet SRA needs. External obstacles are in the form of the negative influence of the free culture of the community and the not yet optimal participation of parents in supporting Child Friendly Schools. Internal obstacles are overcome by communicating and disseminating understanding of Child Friendly Schools to both students and teachers, while external obstacles are overcome by implementing character values in online learning, often involving the police through Babinkamtipmas and communication approaches with parents and guardians.